Grand challenges for research in the Laurentian Great Lakes. (15th June 2017) - Sterner, Robert W.; Ostrom, Peggy; Ostrom, Nathaniel E.; Klump, J. Val; Steinman, Alan D.; Dreelin, Erin A.; Vander Zanden, M. Jake; Fisk, Aaron T.
Abstract: The Laurentian Great Lakes (LGL) constitute one of the largest freshwater systems in the world while providing social and economic value to two powerful nations. The spatial scale of these inland seas falls between two endpoints: small lakes and oceans. Lacustrine in many characteristics, the LGL often require a scientific approach with attributes similar to those of oceanography. There is a strong sense that within the LGL support for scientific research has not kept pace with the need for process‐oriented research and that we lack basic information needed to forecast change, mitigate impacts and restore and preserve the LGL. Consequently, 58 researchers met in September 2014 and identified five "Grand Challenges for Research in the LGL": (1) How has this vast inland freshwater system responded to shifting climate in the past, and how will it respond in the future? (2) What is the current status of the most important ecosystem processes, including their variability in space and time? (3) What processes are characteristic only of large lakes, and how do the distinct habitats integrate into a whole? (4) What are the ecosystem responses to major anthropogenic forces such as nutrients and invasive species, and are these reversible? and (5) What are the small to large‐scale linkages and feedbacks among societal decisions, biological systems, and physicochemical dynamics? An urgent need exists for a unified scientific voice that articulates the Grand Challenges for research in the LGL and the need for associated funding. This treatise describing the Grand Challenges develops that voice.